Design and Synthesis of Selective Modulators for N3-Subunit-Containing NMDA Receptors - Karim,Samer (2025)
NMDA receptors are ligand-gated ion channels assembled as heterotetramers composed of glycine-binding GluN1 and GluN3 subunits (GluN3A-B), and glutamate-binding GluN2 subunits (GluN2A-D). Their involvement in various psychiatric and neurological disorders makes them potential therapeutic targets. However, compared to the extensively studied GluN1/2 NMDARs, the functional, physiological, and pharmacological characteristics of GluN1/3 NMDARs remain poorly understood. Here, we describe the design and synthesis of a series of analogous derived from two previously identified allosteric modulators (A and C) developed in the Rasmus group, followed by two novel competitive antagonists derived from the previously reported compounds, DCKA and MDL-104,653, to target GluN3-containing NMDA receptors. Different synthetic routes have been developed to efficiently synthesise the allosteric modulators and competitive antagonists, with varying degrees of difficulty regarding chemo- and regioselectivity. Further studies to evaluate the pharmacological activity of the 19 novel analogues are still ongoing.
Keywords: Allosteric modulator; Competitive antagonist; GluN3 subunit; NMDA receptor; Organic chemistry